2008
DOI: 10.1128/aem.01491-08
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of α-Methylacyl Coenzyme A Racemase from Gordonia polyisoprenivorans VH2

Abstract: The mcr gene of Gordonia polyisoprenivorans VH2 is not clustered with genes required for rubber degradation. Its disruption by insertion of a kanamycin resistance cassette impaired growth on methyl-branched isoprenoids but not on linear hydrocarbons. Intact mcr from this bacterium or from Nocardia farcinica IFM 10152 complemented the mutant. Reverse transcription analysis showed similar mcr VH2 expression results during cultivation with poly(cis-1,4-isoprene) and propionate. Additional genes coding for a putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Another transposon-induced mutant, which could no longer grow on IR, showed the involvement of an Mce cluster that seems to be involved in the transport of the oligomers generated outside the cell. Our proposal of a further degradation of the cleavage products similar to the degradation of fatty acids is consistent with mutants of strain VH2 generated in the past (5,9) and is supported by analysis of the genome sequence. The genome harbors an extensive number of putative genes involved in ␤-oxidation.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Another transposon-induced mutant, which could no longer grow on IR, showed the involvement of an Mce cluster that seems to be involved in the transport of the oligomers generated outside the cell. Our proposal of a further degradation of the cleavage products similar to the degradation of fatty acids is consistent with mutants of strain VH2 generated in the past (5,9) and is supported by analysis of the genome sequence. The genome harbors an extensive number of putative genes involved in ␤-oxidation.…”
Section: Resultssupporting
confidence: 65%
“…The next step is most likely catalyzed by one of the two ␣-methylacyl-CoA racemases (GPOL_c25180, GPOL_c36450) located in the genome. In previous studies, one Mcr (GPOL_c36450) was found to be essential for strain VH2, since a disruption led to a total loss of the ability to utilize rubber for growth (5). This Mcr catalyzes the conversion of the (R)-into the (S)-stereoisomer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations